International Scientific Migration: Progress or a Threat to Russia’s Scientific and Technological Security - Koksharov, Viktor Anatolyevich; Agarkov, Gavriil Aleksandrovich (Economy of Regions, 2018)
The authors focus on the issues of scientific migration. This trend is relevant from both an academic perspective - studying the individual’s economic behaviour, as well as practical one, because competition for talent has a significant impact on innovation policy initiatives around the world. Most Russian and foreign researchers are unanimous about the main complication for these studies: the lack of reliable information about scientific researchers’ migration. To search for these data, we have developed a methodology implemented in software based on the big data technology. This software allows to analyse data sets from leading scientific citation bases. The information on scientific migration resulted from the analysis of changes in affiliation. We have collected the data on the scientific migration of researchers employed by the Ural Federal University from the Scopus database. The verification of the obtained data showed their high reliability. Most researchers move to Western European countries and the United States (up to 72 %). The main areas of emigrating researchers’ scientific interests are natural and technical sciences. The optimal approach to minimizing the negative impact of scientific migration on Russia’s scientific and technological security is the practical application of the theory of brain sharing. According to this theory, a large scientific diaspora abroad is an essential resource for the development of science and innovation.